2018
DOI: 10.5455/medarh.2018.72.456-458
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Aspergillosis After Kidney Transplant - Treatment Approach

Abstract: Aim: Aim of the article was to present a case of post transplantation invasive aspergillosis, successfully treated with conservative and surgical treatment. Case report: Patient, male, 44 years old, with second kidney transplant, required special preparation therapy, because he was sensitized, with concentration of Panel Reactive Antibody (PRA) class I 11% and PRA class II 76%. On the day of transplantation, induction was done with anti - … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The effect of the newly introduced pathogens is particularly threatening in transplant patients and other immunesuppressed hosts [6] . Application GM test that detects existence of antibodies against Aspergillus antigens and usage of different type of immunosuppressive preparation can increase longevity of graft and patients in solid organ transplantation program [7] .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the newly introduced pathogens is particularly threatening in transplant patients and other immunesuppressed hosts [6] . Application GM test that detects existence of antibodies against Aspergillus antigens and usage of different type of immunosuppressive preparation can increase longevity of graft and patients in solid organ transplantation program [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Although the incidence rates are low at 0.5% in most published examples, they range from 0.2% to 14% in different studies [ 9 , 10 , 11 ]. It is also observed that the reported incidence of IA after renal transplantation varies from region to region across the globe.…”
Section: Introductionmentioning
confidence: 99%
“…A high mortality rate has been observed in IA in renal transplants (40–60%) [ 1 , 12 ]. In some studies, it is as high as 67% to 92%; however, this may be due to the small number of cases of these studies [ 7 , 11 , 13 ]. For example, Gavalda et al observed the death of 7 out of 10 renal transplant recipients with IA in his retrospective case–control study, a 70% mortality [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations